Mini PCNL for renal calculi: does size matter?. (May 2017) - Hennessey, Derek B.; Kinnear, Ned K.; Troy, Andrew; Angus, David; Bolton, Damien M.; Webb, David R.
Abstract : Objective: To evaluate the minimally invasive percutaneous nephrolithotomy (MIP) system for renal calculi. Patients and Methods: Consecutive patients undergoing mini‐percutaneous nephrolithotomy (mPCNL) procedures with the MIP system were enrolled. Patient position, American Society of Anesthesiologists classification, puncture location, stone clearance, postoperative drainage and complications were recorded, and features unique to MIP were noted. Results: In all, 30 patients underwent 32 mPCNL procedures. The mean stone size was 17 (10.75–21.25) mm and the mean number of stones was 1 (1–2). The median stone clearance rate was 96.5 (95–100)%. The complication rate was 9.3%. No patient required a transfusion. In addition to these outcomes, we noted that the MIP system has many advantages over conventional PCNL (cPCNL). It is easy to learn and can be performed in both supine and prone positions. It is safe for supracostal puncture, provides excellent access to nearly all calyces and upper ureter, has multiple stone treatment options, can be used as an adjunct to cPCNL, and can be performed as a tubeless procedure. Conclusion: Our experience with the MIP system has shown several advantages over cPCNL. mPCNL with the MIP system has several features that suggest it should be considered as an alternative or adjunct to cPCNL, ureteroscopy and extracorporeal shockwave lithotripsy.